Advancements in dental bioreactor design: A comprehensive approach for application in dentistry - Esteban Astudillo-Ortiz; Pedro S. Babo; Ana I. Gonçalves; Manuela E. Gomes (MethodsX)
The protocol introduces a novel multi-chamber bioreactor tailored for ex-vivo cell culture in dentistry research, emulating the 3D dental environment to propel research in dental applications. Constructed primarily from a polymeric material with a sophisticated 3D design, the bioreactor securely holds teeth structures within sealed chambers, enabling controlled perfusion of culture medium crucial for cell growth through a singular entry and exit point. An integrated electronic system manages flow and pressure, ensuring precise control over environmental conditions. This technology facilitates cell cultivation under conditions closely resembling natural tooth microenvironments, offering opportunities for varied studies from understanding cellular behavior in dental contexts to targeted therapy development. The bioreactor's amalgamation of polymeric components, 3D design, and electronic controls enhances adaptability and accuracy, rendering it a valuable asset in dental research. The report comprehensively delineates the bioreactor's design, operations, and potential applications, showcasing its significant contributions to dental research and regenerative medicine. By amalgamating advanced technologies, this bioreactor emerges as a pivotal tool for investigating cellular processes within dental structures, paving the way for scientific exploration and therapeutic advancements.